Cone and rod dysfunction in the NARP syndrome. Issue 2 (1st February 1999) - Chowers, Itay; Lerman-Sagie, Tally; Elpeleg, Orly N; Shaag, Avraham; Merin, Saul
Abstract : AIMS: Description of the ophthalmic manifestations of the NARP (neuropathy, ataxia, retinitis pigmentosa) syndrome that is associated with a point mutation in position 8993 of the mitochondrial DNA (mtDNA). METHODS: A mother and her two children, all carrying the 8993 mtDNA mutation, were examined. Two had manifestations of the NARP syndrome. A complete ocular and systemic examination was performed on all three patients. RESULTS: The clinical examination, electroretinogram, and visual fields revealed a typical cone-rod dystrophy in the son, and a typical cone dystrophy in the daughter. The mother had no ocular manifestations of the disease. CONCLUSIONS: NARP is a recently described, maternally inherited mitochondrial syndrome in which a retinal dystrophy, among other abnormalities, is related to a mutation of the mtDNA at nucleotide 8993. This study demonstrates the great variability of the ocular manifestations in the NARP syndrome. It also indicates that the retinal dystrophy in at least some NARP patients affects primarily the cones.